Pengaruh Tandem Walking Exercise Terhadap Keseimbangan Lansia Di Panti Tresna Werdha Inakaka, Kota Ambon - Valensya Yeslin Tomasoa; Reni Chairani; Syamsul Anwar (FORIKES, 2021)
Background: Physical activity includes high mobilization, which is an activity that can improve body balance, such as tandem walking exercise. The purpose of this study was to determine the effect of tandem walking exercise on the balance of the elderly at the Tresna Werdha Ina-kaka Home, Ambon City. Methods: This study was a quasy experimental study with a pre-test design and a post control group design. Sampling using purposive sampling technique of 42 elderly who were taken randomly and divided into 2 groups, namely the intervention group and the control group. Results: Pairet T Test analysis showed a significant difference in the balance of the elderly before and after Tandem walking exercise was given in the intervention group with p value 0.05. In the General Linier Model-Repeated Measures (GLM-RM) analysis, it was found that the balance of the pure intervention group had an increase in the balance of the p-value = 0.000, while the pure control group did not experience an increase in the balance of p value => 0.05. Conclusion: The results of this study are expected to be used as a program for nurses and nursing staff to improve the balance of the elderly. Keywords: balance; elderly; tandem walking exercise ABSTRAK Latar belakang: Aktivitas fisik termasuk mobilisasi tinggi yang merupakan kegiatan yang dapat meningkatkan keseimbangan tubuh, seperti Tandem Walking Exercise. Tujuan penelitian ini adalah mengetahui pengaruh Tandem Walking Exercise terhadap keseimbangan lansia di Panti Tresna Werdha Ina-kaka, Kota Ambon. Metode: Penelitian ini merupakan penelitian quasy experimental dengan desain pre-test dan post control group design. Pengambilan sampel menggunakan teknik purposive sampling pada 42 lansia yang dipilih secara random dan dibagi menjadi 2 kelompok yaitu kelompok intervensi dan kelompok kontrol. Hasil: Analsis Pairet T Test menunjukkan perbedaan bermakna keseimbangan lansia sebelum dan sesudah diberikan Tandem walking exercise pada kelompok intervensi dengan p value 0,05. Pada analisis General Linier Model-Repeated Measures (GLM-RM) didapatkan hasil keseimbangan kelompok intervensi murni mengalami peningkatan keseimbangan nilai p-value = 0,000, sedangkan untuk kelompok kontrol murni tidak mengalami peningkatan keseimbangan p value = > 0,05. Kesimpulan: Hasil penelitian ini dijadikan sebuah program perawat dan petugas panti untuk meningkatkan keseimbangan lansia. Kata kunci: keseimbangan; lansia; tandem walking exercise